Extensional Polarity Change in Continental Rifts: Inferences From 3‐D Numerical Modeling and Observations. Issue 9 (4th September 2018) - Balázs, A.; Matenco, L.; Vogt, K.; Cloetingh, S.; Gerya, T.
Abstract: Extensional basins often show along‐strike variability in terms of fault geometries, basement structures, subsidence, and thermal evolution. This is particularly pronounced when extension reactivates preexisting suture zones with opposing dip directions, that is, opposite polarities, which creates wide strike‐slip transfer zones. We have studied this extensional variability by means of thermomechanical lithospheric‐scale 3‐D numerical modeling. We conducted a series of experiments to model the extension of a thick lithosphere simulating a young orogenic area containing segmented suture zones inherited from former opposing subduction polarities, implemented as rheologically weak inclined layers with opposite dips. Numerical experiments demonstrate that the initial subduction sutures are reactivated by two long‐lived lithospheric‐scale detachment faults, which remain active until the onset of oceanic spreading. The opposite polarity of these faults causes their migration toward each other by asymmetric mantle lithosphere extension and thermal accretion. Crustal kinematics shows the formation of extensional detachment faults and high‐offset listric normal faults. These structures undergo gradual tilting during their footwall exhumation, while the rheological weak suture layers are redistributed beneath the crust. The results demonstrate an active interaction along the strike of the system between the two opposite dipping weak zones, where fault segments mechanically interact. During extension, the maximum horizontal fault offset switches the apparent sense of shear in the separating strike‐slip transfer zone. This kinematics explain the rapid change in the sense of shear in major strike‐slip transfer zones or transform faults, such as observed during the extension of the Pannonian back‐arc basin. Key Points: We have conducted 3‐D lithospheric‐scale numerical modeling of rift interaction Extensional reactivation of lithospheric‐scale suture zones has been analyzed Strike‐slip transfer faults evolve and change their sense of shear with time